2020
DOI: 10.3390/ijms21197223
|View full text |Cite
|
Sign up to set email alerts
|

Dicing the Disease with Dicer: The Implications of Dicer Ribonuclease in Human Pathologies

Abstract: Gene expression dictates fundamental cellular processes and its de-regulation leads to pathological conditions. A key contributor to the fine-tuning of gene expression is Dicer, an RNA-binding protein (RBPs) that forms complexes and affects transcription by acting at the post-transcriptional level via the targeting of mRNAs by Dicer-produced small non-coding RNAs. This review aims to present the contribution of Dicer protein in a wide spectrum of human pathological conditions, including cancer, neurological, a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
16
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 24 publications
(16 citation statements)
references
References 183 publications
(260 reference statements)
0
16
0
Order By: Relevance
“…13 Erroneous expression of DICER1 has also been associated with autoimmune disorders with both loss and upregulation contributing to a range of pathologies including ankylosing spondylitis, psoriasis, rheumatoid arthritis, multiple sclerosis and autoimmune thyroid disorders. 14 Potentially more subtle effects of timing and extent of gene expression during embryogenesis could contribute to human facial variation as, in a study by Liu et al, SNP rs7161418 in DICER1 was one of 12 SNPS from 10 genes significantly associated with facial morphology in the Han Chinese populations. 15 Ageing is associated with decreased expression of DICER1 and changes in its diurnal expression pattern.…”
Section: Gene Expressionmentioning
confidence: 99%
“…13 Erroneous expression of DICER1 has also been associated with autoimmune disorders with both loss and upregulation contributing to a range of pathologies including ankylosing spondylitis, psoriasis, rheumatoid arthritis, multiple sclerosis and autoimmune thyroid disorders. 14 Potentially more subtle effects of timing and extent of gene expression during embryogenesis could contribute to human facial variation as, in a study by Liu et al, SNP rs7161418 in DICER1 was one of 12 SNPS from 10 genes significantly associated with facial morphology in the Han Chinese populations. 15 Ageing is associated with decreased expression of DICER1 and changes in its diurnal expression pattern.…”
Section: Gene Expressionmentioning
confidence: 99%
“…It has been found that when DICER1 gene is mutated, through inherited or acquired mutation, patients develop an increased predisposition to thyroid tumor development. Patients with germline inherited DICER1 loss-of-function mutations could suffer from a wide variety of rare life-threatening childhoodonset malignancies, such as benign and malignant thyroid neoplasms including PTC, collectively called DICER1 syndrome (75). Also, acquired somatic mutations or downregulation of DICER1 expression have been found in earlyadulthood-onset well differentiated thyroid cancer (PTC and follicular thyroid cancer) and poorly differentiated thyroid carcinoma.…”
Section: Discussionmentioning
confidence: 99%
“…MicroRNA appears to mediate most EV effects [ 159 ] by three known mechanisms: [ 1 ] Binding the 3’UTR of their target mRNA, silencing the gene and blocking translation, [ 2 ] Translational repression by cleaving and degrading mRNA, [ 3 ] De-adenylation and degradation of mRNAs [ 160 ]. The miRNA processing endonuclease Dicer is a member of the ribonuclease III family that functions in the RNA interference pathway to cleave long double stranded RNA molecules into small RNAs including miRNA and siRNA [ 161 , 162 ]. Dicer1 is essential to the miRNA pathway and Dicer2 facilitates the siRNA pathway [ 161 ].…”
Section: Main Textmentioning
confidence: 99%
“…Dicer1 is essential to the miRNA pathway and Dicer2 facilitates the siRNA pathway [ 161 ]. Dicer cleaves the precursor miRNA (pre-miRNA) hairpins at the stem-loop boundary, generating mature miRNA [ 162 ]. ADicer knockout mice (ADicerKO) lack effective miRNA processing in adipose tissue.…”
Section: Main Textmentioning
confidence: 99%